1981
DOI: 10.1073/pnas.78.5.2683
|View full text |Cite
|
Sign up to set email alerts
|

Differential inhibition of multiple forms of DNA polymerase alpha from IMR-32 human neuroblastoma cells.

Abstract: Three forms of DNA polymerase (pol) a from human neuroblastoma IMR-32 were separated by DEAE column chromatography. All sedimented at -7 S in 5-20% continuous sucrose density gradients. All were heat labile, with pol a2 the most (90% inactivated) and pol a3 the least (50% inactivated) sensitive to heating for 5 min at 50TC. pol a, and a2 efficiently utilized activated calf thymus DNA as template. The most active form, pol a2, used both poly(dA)-(dT)j2_j8 and poly(dT)-(dA)12_18 as template at equal rates. Diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

1982
1982
2008
2008

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…As mentioned above, hemin has been shown to inhibit retroviral RT and other DNA polymerases (6,35). We have also found that hemin and the related porphyrin compounds could inhibit the purified Moloney murine leuke-mia virus RT and the Klenow fragment of the Escherichia coli DNA polymerase I with a potency only slightly less than their inhibitory effects on the HBV and DHBV RT (Li and Hu, unpublished).…”
Section: Discussionmentioning
confidence: 71%
“…As mentioned above, hemin has been shown to inhibit retroviral RT and other DNA polymerases (6,35). We have also found that hemin and the related porphyrin compounds could inhibit the purified Moloney murine leuke-mia virus RT and the Klenow fragment of the Escherichia coli DNA polymerase I with a potency only slightly less than their inhibitory effects on the HBV and DHBV RT (Li and Hu, unpublished).…”
Section: Discussionmentioning
confidence: 71%
“…The primase subunit, closely associated with DNA polymerase a, initiates RNA primers before any DNA chain initiation in mouse tumor cells (4,5), Drosophila (6,7), Xenopus laevis (8), human KB cells (9), yeast (10)(11)(12)(13)(14), calf thymus (15,16), human IMR-32 neuroblastoma cells (17), and embryonic chicken brain (54). In addition to primase activity, multiple forms of DNA polymerases (18)(19)(20)(21)(22)(23)(24) from various eukaryotic sources appear to contain specific proteins (25)(26)(27)(28). The DNA polymerase a isolated from different animal sources (25) appears to be homogeneous on native polyacrylamide gels.…”
mentioning
confidence: 99%
“…The existence of multiple forms of DNA polymerase a activity in normal and tumor cells has been well established (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12), but it is not yet clear whether these multiple forms arise from a single native protein. However, studies with two highly purified species of DNA polymerase a from mouse myeloma cells have indicated the presence of two different subunits that failed to show any sequence homology on tryptic peptide maps (8).…”
mentioning
confidence: 99%
“…In contrast, Hesslewood et al (6) have shown that one form of rat liver DNA polymerase a activity could be converted to a second form by exposure to mild urea treatment. Recently, we have shown the presence of three forms of DNA polymerase a activity in cultured human neuroblastoma IMR-32 cells (12,13). They all sediment at approximately 7 S but have different template-primer preferences and heat sensitivities (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation